Epigenetic methylation changes: implication as biomarkers in oral and maxillofacial area cancers - Aghiorghiesei, Ovidiu; Irimie, Alexandra Iulia; Braicu, Cornelia; Raduly, Lajos; Nutu, Andreea; Balint, Emilia; Mehterov, Nikolay; Vladimirov, Boyan; Sarafian, Victoria; Lucaciu, Ondine; Campian, Radu; Berindan-Neagoe, Ioana (Medicine and Pharmacy Reports, 2023)
Background/Aim. Squamous cell carcinoma (SCC) is the most frequent cancer of the head and neck area in the oral cavity. Epigenetic alterations in oral and maxillofacial area cancers are urgently needed to be investigated, as the observed changes might have crucial diagnostic value for personalized medicine. Methods. Our study aimed to identify the most frequently hypermethylated tumor suppressor gene promoters in OSCC, followed by correlation analysis with the patients’ survival. We evaluated the methylation status of the promoters in a panel of 22 tumor suppressor genes in Romanian (n=9) and Bulgarian (n=12) patient groups suffering from oral and maxillofacial area cancers. The extracted DNA was further digested through EpiTect Methyl II PCR Array System containing methylation-sensitive and methylation-dependent restriction enzymes, followed by specific amplification of the products obtained by qPCR and data analysis using the online platform provided by the producer. Results. Different methylation patterns were observed in the tumor suppressor genes’ promoters. Among them, the methylation profile of Cccnd2, Chd1, Cdh13, Cdkn1c, Neurog1, Gstp1, and Runx3 genes further correlated with overall survival rates. Conclusions. Our data emphasize that epigenetic alterations are responsible for the clinical heterogeneity of oral and maxillofacial area cancers and significantly impact on patient survival. Additional investigation on a larger patient cohort should validate these potential biomarkers.